Economic Impact of Imposing Excise Tax on Plastic Bottles of Drinks - Eugenia Mardanugraha (Economics and Finance in Indonesia, 2017)
This research simulates the effect of imposing excise tax on plastic container of drinks towards economic performance of beverage industry in Indonesia and governmentâ˘A ´Zs tax revenue. The results showed that by imposing excise tax on plastic cups and plastic bottles the government would lose tax revenue from value added tax (PPN) and corporate income tax (PPh badan) more than they gain additional revenue from excise tax. Hence, imposing excise tax on drink containers should serve a clear purpose and an undeniable reason. This paper recommends the government to develop proper excise infrastructure to extend the goods or services to be taxed. This paper also recommends the required stages for extending the excise tax.